A SYSTEMATIC LITERATURE REVIEW ON THE INTERNATIONALIZATION OF SMALL AND MEDIUM-SIZED ENTERPRISES ON THE AFRICAN CONTINENT - SITHOLE, Mbali Ayanda (Studia Universitatis Babeș-Bolyai Negotia, 2025)
This study aimed to identify prominent themes discussed in the research on the internationalization of SMEs on the African continent from 2005 to 2023. For this study, a total of 50 articles were selected, and thematic analysis was conducted to identify the prominent themes. Among the fifty articles selected for this systematic literature review (SLR), seven prominent themes were found: pull factors, network theory, export performance, mindset, entry mode decision, institutions, and barriers to internationalization. In this sample of articles, the most discussed themes are pull factors, network theory, and export performance, while the least discussed is barriers to internationalization. The findings of this study suggest that further research should be conducted to examine how the mindset of entrepreneurs or top managers may affect the internationalization of African SMEs, and how this may also affect the mode of entry adopted bysmall and medium size enterprises (SMEs). In addition, further research should be conducted on the barriers to internationalization of SMEs on the African continent. Lastly, this study recommends that further research be conducted on the role that institutions play in facilitating the internationalization of SMEs in Africa. The significant contribution of this study was identifying the prominent themes concerning internationalization in the African context. In addition, it identified areas for further research in order to gain a deeper understanding of this phenomenon in Africa. JEL Classification: F23, L26, O55 Article History: Received: 20 February 2025; Reviewed: 30 May 2025; Accepted: 20 June 2025; Available online: 27 June 2025